Male Circumcision, What Millennial Parents Considering Perceived Value on Circumcision Clinic Decision Choices - Perdana, Noor Riza; Meilani, Yohana Palupi (Syntax Literate, 2024)
Perceived value is the difference between prospective customers assessments of all the benefits and costs of an offer to its alternatives. Perceived value, according consists of several main aspects, namely functional value, emotional value, socialvalue, religious value, epistemic value and economic value. These aspects of perceived value can influence the decision of a consumer to use or buy goods or services. The purpose of this study was to determine the factors that influence millennial parent decision choice on choose circumcision clinic. From the total of 270 respondents, there were 158 male respondents and 112 female respondents. The majority group of respondents was in the range 36 – 41 years old. In term of education 89,63with S1. This study show social value, religious value and epistemic value has positive and significant influence on the decision choice of millennial parents in choosing a circumcision clinic. Functional value, emotional value and economicvalue, in this study has no effect on decision choice.